Parecoxib mitigates lung ischemia-reperfusion injury in rats by reducing oxidative stress and inflammation and up-regulating HO-1 expression - Qin,Jun (2021)
ABSTRACT Purpose: To investigate the protective effect of parecoxib against lung ischemia-reperfusion injury (LIRI) in rats and the mechanism. Methods: Thirty rats were divided into sham-operated, LIRI and LIRI+parecoxib groups. LIRI model (ischemia for 60 min, followed by reperfusion for 120 min) was constructed in LIRI and LIRI+parecoxib groups. In LIRI+parecoxib group, 10 mg/kg parecoxib was given via femoral vein 15 min before ischemia beginning. At the end of the reperfusion, blood gas analysis, lung wet to dry mass ratio measurement, lung tissue biochemical determination and heme oxygenase-1 (HO-1) protein expression determination were performed. Results: Compared with LIRI group, in LIRI+parecoxib group the oxygenation index was significantly increased, the alveolar-arterial oxygen partial pressure difference was significantly decreased, the lung wet to dry mass ratio was significantly decreased, the lung tissue malondialdehyde content was significantly decreased, the lung tissue superoxide dismutase and myeloperoxidase activities were significantly increased, the lung tissue tumor necrosis factor α and interleukin 1β levels were significantly decreased, and the lung tissue HO-1 protein expression level was significantly increased (all P < 0.05). Conclusions: Parecoxib pretreatment can mitigate the LIRI in rats by reducing oxidative stress, inhibiting inflammatory response and up-regulating HO-1 expression in lung tissue.